Sparstolonin B nano-formulation attenuates LPS-induced lung injury - Meng, Qinghe; Wang, Xiaojing; Guo, Dandan; Zhang, Gary; Shi, Changying; Novak, Adam; Yang, Xiguang; Luo, Juntao; Cooney, Robert N. (Frontiers in Pharmacology, 2025)
IntroductionNanomedicines can improve drug delivery and efficacy while reducing side effects. Our study examines the impact of a nano-formulation of Sparstolonin B (nSsnB), a TLR-4 antagonist, on LPS-induced inflammation in RAW264.7 cells and lung injury in mice.MethodsRAW264.7 cells were treated with LPS (1 μg/mL) ± nSsnB (2–64 μg/mL) for 24 h. Cell viability was assessed, cytokine levels in media were measured, and cell lysates were used to quantify NF-κB activation. C57BL/6 mice were treated with prophylactic intratracheal (IT) nSsnB (0.625 mg/kg) ± IT LPS (2.5 mg/kg). Blood and BALF were collected for cytokine, protein and cytological analysis. Lung histology was scored to evaluate lung injury. The relative abundance of MyD88 and phosphorylated NF-κB were measured in lung and HLL mice were used to measure NF-κB activation in vivo.ResultsnSsnB demonstrated reduced toxicity vs. free SsnB. nSsnB ameliorated the LPS-induced increase in TNF-α, IL-6 and NF-κB P65 phosphorylation in RAW264.7 cells. LPS-treated mice revealed histologic ALI, elevated BALF neutrophils/macrophages/total protein, and increased levels of TNF-α/IL-6 in both BALF and plasma. Prophylactic nSsnB attenuated all these parameters in the LPS/nSsnB group. The increased levels of MyD88 and P-NF-κB P65 in lung from LPS-treated mice were reduced in the LPS/nSsnB group and nSsnB attenuated the increase in NF-κB activation induced by IT LPS in HLL mice.ConclusionnSsnB demonstrates less toxicity than free SsnB and attenuates the effects of LPS on inflammation in RAW264.7 cells. Prophylactic nSsnB attenuates LPS-induced ALI by reducing inflammation via MyD88/NF-κB signaling pathways. Collectively these findings support the therapeutic potential of nano-formulated nSsnB for ALI treatment.